2015
DOI: 10.1128/mbio.02110-14
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Products of the Extracellular Pathogen Streptococcus pneumoniae Access the Cytosol via Its Pore-Forming Toxin

Abstract: Streptococcus pneumoniae is a leading pathogen with an extracellular lifestyle; however, it is detected by cytosolic surveillance systems of macrophages. The innate immune response that follows cytosolic sensing of cell wall components results in recruitment of additional macrophages, which subsequently clear colonizing organisms from host airways. In this study, we monitored cytosolic access by following the transit of the abundant bacterial surface component capsular polysaccharide, which is linked to the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 40 publications
0
62
0
Order By: Relevance
“…We have previously reported that infection of macrophages with a type 23F strain of S. pneumoniae results in host cell death, subsequent to bacterial uptake and pneumolysin-dependent cytosolic access of pneumococcal fragments (12). To determine whether pneumolysin-dependent cytosolic access causes proinflammatory cytokine release upon in vitro infection, we incubated bone marrow-derived macrophages (BMMs) with the wild-type (WT) 23F isolate and 24 h later assayed for the presence of IL-1␤ in the cell culture supernatants by Western blotting.…”
Section: Pneumococcal Infection Results In Il-1 Family Cytokine Exprementioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that infection of macrophages with a type 23F strain of S. pneumoniae results in host cell death, subsequent to bacterial uptake and pneumolysin-dependent cytosolic access of pneumococcal fragments (12). To determine whether pneumolysin-dependent cytosolic access causes proinflammatory cytokine release upon in vitro infection, we incubated bone marrow-derived macrophages (BMMs) with the wild-type (WT) 23F isolate and 24 h later assayed for the presence of IL-1␤ in the cell culture supernatants by Western blotting.…”
Section: Pneumococcal Infection Results In Il-1 Family Cytokine Exprementioning
confidence: 99%
“…Although S. pneumoniae is an extracellular pathogen, this macrophage influx is the result of intracellular innate immune recognition by the cytosolic Nod-like receptor 2 (Nod2) (9). Nod2 detects peptidoglycan (10,11) that accesses the macrophage cytosol via the pneumococcal poreforming toxin pneumolysin following phagocytosis and bacterial degradation (12). Nod2 activation results in nuclear factor B (NF-B) activation (13) and drives proinflammatory cytokine production, including the C-C motif chemokine ligand 2 (CCL2), which contributes to monocyte/macrophage-dependent pneumococcal clearance (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Last, we examined whether the minimal PG turnover was altered by ⌬pgdA or ⌬adr mutation, each of which alters PG glycan chain modification and, thus, could potentially serve as a turnover signal. PgdA deacetylates GlcNAc in the PG glycan chains of wild-type cells, thereby imparting resistance to host lysozyme produced by the innate immune response (23,39,64). Adr O-acetylates the 6 position of MurNAc in PG glycan chains, which imparts lysozyme and penicillin resistance to strains of some serotypes (38,64).…”
Section: Figmentioning
confidence: 99%
“…For some phagocytosed extracellular pathogens, such as Streptococcus pneumoniae (pneumococcus), lysozyme digestion concomitantly produces PG fragments and releases a pore-forming toxin that damages the phagosome membrane (23). This damage enables the release of PG fragments into the cytosol, where they can interact with Nod2 receptors that induce proinflammatory signaling, leading to the recruitment of additional phagocytic cells to infection sites (23).…”
mentioning
confidence: 99%